Use of Music Intervention for Reducing Anxiety and Promoting Satisfaction in First-Time Filipino Fathers. (March 2016) - Labrague, Leodoro J.; McEnroe-Petitte, Denise M.
Childbirth is an anxiety-provoking event in a man's life. Therefore, strategies to decrease paternal anxiety during childbirth are necessary. This study determined the effects of music and satisfaction of first-time Filipino fathers during childbirth. In the study, a prospective quasi-experimental design was utilized. Ninety-eight purposive samples of first-time fathers were included in the study, 50 were allocated in the experimental group (music group) and 48 in the control group (nonmusic group) during the months of August to October 2013. Paternal anxiety and satisfaction were measured using the State Trait Anxiety Inventory and the Visual Analogue Scale for Satisfaction, respectively. Results revealed that the first-time fathers in the experimental group had lower State Trait Anxiety Inventory scores ( p < .05) and higher Visual Analogue Scale for Satisfaction scores ( p < .05) than those in the control group. Findings of the study provide substantial evidence to support the use of music in reducing anxiety and promoting satisfaction among first-time fathers during childbirth.